"Infome de implementación de la unidad de cuidados intensivos pediátricos. Hospital Belen de Trujillo" - Benites Carbajal, Estela Elizabeth (2012)
I project the present of Intervención 2009-2010, due to the need to count on a destined area to the critically sick intensive care of the pediatric patient, whose request has increased of late years even came true in Pediatría's service of Trujillo's Hospital Belén ( HBT ) during the year the present time. The project was presented to the authorities of the hospital, professional staff and professional no of Pediatría's service that was accepted and you allowed, he accomplishing meetings for the start of activities like the committees' conformation: Of step, capacitation, implementation and of the strengthening of the service. Four lines of action were used like strategy, whose results are: Approval of Intervención's Project for the Management of Trujillo's Hospital Bethlehem the same that was sent to Salud's Regional Management and Regional Government of Freedom, habilitation of the infrastructure of the environment destined for the pediatric UCI, aparatajes's acquisition and biomedical teams, the educational program was executed for the staff of the service, elaborated themselves and they distributed, the project's educational and diffusion material, records and protocols; In like manner programming of internships shows up for the staff of Pediatría's service. The project at present continues on execution.